(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
This paper is dealing with the stratigraphical position of the main fossil Vertebrate localities from the Italian Triassic. Recent and new data are summarized to give a sure age to old—known localities as well as to recently discovered ones. Besano—Mt. S. Giorgio (Anisian—Ladinian), Perledo (Ladinian—? Lower Carnian), Raibl (Lower Carnian), Ca’ del Frate (Lower Carnian), Preone Valley (Lower Norian), Brescia and Bergamo Prealps (Norian) and Giffoni Valle Piana (Norian) are the investigated localities. Field works are still in progress in several sites, mainly by the authors.